Comparision outcome of sublingual and vaginal misoprostol for induction of labour at postterm in Samutsakhon hospital - Chantrarangsan, Prae (Journal of Medicine and Health Sciences, 2023)
Induction of labor at postterm is the most common obstetric practice. Traditional oral and vaginal misoprostol are effective induction methods, but there is a delicate balance between successful rate, maternal and fetal safety, as well as convenience and savings. This ramdomized controlled trial method aims to compare the efficacy of vaginally administered and sublingual misoprostol for outcomes of induction delivery interval, maternal and fetal outcomes. Sixty-four pregnant women at postterm who fulfilled the inclusion criteria were equally randomized into the two groups to receive misoprostol 25 mcg sublingually or 25 mcg vaginally. The statistics were analyzed using a Chi-square test and an independent t-test. The results found the following: there were no statistical differences in the age, hieght, weight, body mass index number of pregnancies, parity, abortion, gestational age, Bishop score and birth weight in both groups. The mean time from the first dose to achievement of bishop score 7 or active phase was significantly shorter in the sublingual group than the vaginal group (8.33 ± 4.27 vs 10.49 ± 2.98, p = 0.022). The number of doses to achieve active phase the sublingual group was mostly 2 and vaginal group mostly 3 (p = 0.041). Also total number of successful vaginal delivery at 10-16 hour and were more in the sublingual group (61.54% vs 29.63% than the vaginal group, p = 0.028). There were no statistical differences of both groups in induction delivery interval, oxytocin augmentation, total number of successful vaginal delivery, delivery methods, adverse maternal and neonatal outcomes. In conclusion, sublingual misoprostol 25 mcg every 4 hour and a maximum of 4 times is effective for induction of labour at postterm.